Chitosan and chito-oligosaccharide: a versatile biopolymer with endless grafting possibilities for multifarious applications - Mohite, Popat; Shah, Sunny R.; Singh, Sudarshan; Rajput, Tanavirsing; Munde, Shubham; Ade, Nitin; Prajapati, Bhupendra G.; Paliwal, Himanshu; Mori, Dhaval D.; Dudhrejiya, Ashvin V. (Frontiers in Bioengineering and Biotechnology, 2023)
Chito-oligosaccharides (COS), derived from chitosan (CH), are attracting rising attention as drug delivery carriers due to their biocompatibility, biodegradability, and mucoadhesive properties. Grafting, the process of chemically modifying CH/COS by adding side chains, has been used to improve their drug delivery performance by enhancing stability, targeted delivery, and controlled release. In this review, we aim to provide an in-depth on recent advances in the grafting of CH/COS for multifarious applications. Moreover, the various strategies and techniques used for grafting, including chemical modification, enzymatic modification, and physical modification are elaborated. The properties of grafted CH/COS, such as stability, solubility, and biocompatibility, were reported. Additionally, the review detailed the various applications of grafted CH/COS in drug delivery, including the delivery of small drugs molecule, proteins, and RNA interference therapeutics. Furthermore, the effectiveness of grafted CH/COS in improving the pharmacokinetics and pharmacodynamics of drugs were included. Finally, the challenges and limitations associated with the use of grafted CH/COS for drug delivery and outline directions for future research are address. The insights provided in this review will be valuable for researchers and drug development professionals interested in the application of grafted CH/COS for multifarious applications.